Granulosa Cell Tumour and Associated Pyometra in an English Mastiff Female Dog - Khokhar, Vishal; Yadav, Dheeraj; Chaudhri, Sumer S.; Chandratre, Gauri A. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Granulosa cell tumour (GCT) is the most common ovarian tumour which can affect 50% of the canine population (Daleck and De Nardi, 2016).These tumors have been categorized as sex cord-stromal tumors, which arise from granulosa cell cords derived from atretic follicles with higher occurrence in middle-aged dogs (Perez-Marin et al., 2014). The main clinical signs in GCT cases include irregular estrous, vaginal bleeding, vaginal hyperplasia, ovarian cyst, pyometra, vaginal prolapse and dermatological lesions such as symmetric alopecia and hyperpigmentation (Tavasoli and Solati, 2011; Perez-Marin et al., 2014). Due to very discrete clinical signs, the diagnosis of ovarian tumors in dogs is usually complicated as it is occasionally confused with other diseases. The histopathological examination is essential for the confirmatory diagnosis of GCT (Matos et al., 2019). This case report describes the occurrence of ovarian granulosa cell tumor and associated pyometra in a female dog presenting for clinical consultation and its diagnosis and treatment.